Factors Related to Practice in Good Agricultural Practices (GAP) of Parsley,s Farmer in Nakhon Sawan Province - Chomngarm, Waraporn; Sukprasert, Patana; Tongchure, Siros; Datepumee, Nuttapon (Princess of Naradhiwas University Journal, 2021)
This survey research was to investigate 1) personal factors and practice in growing parsley of farmers, 2) farmers’ Good Agricultural Practices (GAP) standard compliance and 3) factors related to Good Agricultural Practice (GAP) of parsley,s farmers. Samples were 168 farmers in Nakhon Sawan province, selected by simple random sampling technique. Data were collected through interview, and were analyzed by descriptive statistic such as frequency, percentage, mean, minimum, maximum and Pearson Product Moment Correlation Coefficient. Research findings revealed that most farmers were 66.1% female, average age 54.89 years old, completed primary education 82.7%, having average experience in growing parsley 12.72 year, having average planted area around 6.63 rai. 99.4% of parsley farmers mostly grew in Chanthaburi province, and 56.0% of farmers grew 2 to 3 times per year; from January to April, May to August and September to December. The first plantation produced approximately 1,828.27 kg./rai, the second produced 1,709.21 kg./rai and the third produced 1,000 kg./rai. The average cost was 17,265.48 bath/rai, and the average income was 23,747.02 bath/rai. The household labor used in parsley farming was 1.86 person. The farmers received a high level of GAP in holding, moving produce in planting plot and storage (X = 3.46). It was also found that the farmers have followed some terms of practice in Good Agricultural Practices (GAP) in the areas of household labor, production yield, production cost and income per planted area factors.